2015
DOI: 10.1007/s11663-014-0280-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Electrochemical Investigation of the Corrosion Resistance of Various Alloys Used in Dental Prostheses

Abstract: The electrochemical behaviour of Ag-Pd (Paliag), Ni-Cr (Heraenium NA), and Co-Cr (Heraenium CE) alloys used in dental prosthetics construction of crowns and bridges was studied in 0.9% NaCl solution at 25 ºC. The localized electrochemical characteristics related to corrosion resistance and eventual breakdown of the protecting oxide layers were investigated by scanning electrochemical microscopy (SECM), whereas potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques were employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…With the development of the scanning microelectrochemical microscope (SECM), in vitro studies of the dissolution and passivation reactions of biomaterials can be performed with high spatial 4 and chemical resolution [41][42][43][44][45]. The basic operation principle of the technique consists in the transformation of a redox-active species to another redox state at a microelectrode tip while scanning a surface in close proximity.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the scanning microelectrochemical microscope (SECM), in vitro studies of the dissolution and passivation reactions of biomaterials can be performed with high spatial 4 and chemical resolution [41][42][43][44][45]. The basic operation principle of the technique consists in the transformation of a redox-active species to another redox state at a microelectrode tip while scanning a surface in close proximity.…”
Section: Introductionmentioning
confidence: 99%
“…The potential corrosion values for the investigated alloys were negative. Keeping in mind that positive potentials in the oral cavity could in some cases correspond to a polarization value of 300-400 mV [24], it is evident that NiTi as cast showed unsatisfactory results. The anodic curve for NiTi as cast showed practically only active anodic dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the polar-ization resistance indicates that the corrosion current density decreased. Moreover, if R p changes over time, that indicates some surface processes, usually oxide film formation [24]. The diagram given in Figure 4 represents linear polarization measurements (LPRs) after stabilization of the corrosion potentials of the investigated samples for 2 h. Based on the obtained values, it was demonstrated that NiTicc has a three-times-higher corrosion polarization resistance in comparison with the NiTi as-cast alloy.…”
Section: Samplementioning
confidence: 96%
See 1 more Smart Citation